2014
DOI: 10.1103/physrevd.89.064055
|View full text |Cite
|
Sign up to set email alerts
|

Quantum field theory in the Rindler-Rindler spacetime

Abstract: It is well known that Minkowski vacuum appears as a thermal bath in the Rindler spacetime when the modes on the left wedge are traced out. We introduce the concept of a Rindler-Rindler spacetime, obtained by a further coordinate transformation from the Rindler spacetime, in a manner similar to the transformation from inertial to Rindler frame. We show that the Rindler vacuum appears as a thermal state in the Rindler-Rindler frame. Further, the spectrum of particles seen by the Rindler-Rindler observers in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Subsequently, the particle number, seen by the Rindler frame in thermal bath, was calculated. Later the same authors demonstrated that the particle number seen by the Rindler-Rindler observer in the Minkowski vacuum is identical to this value [16] with the bath temperature is identified as the temperature perceived by the first Rindler frame. In this analysis they studied both particle number computation by Bogoliubov technique and detector response.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Subsequently, the particle number, seen by the Rindler frame in thermal bath, was calculated. Later the same authors demonstrated that the particle number seen by the Rindler-Rindler observer in the Minkowski vacuum is identical to this value [16] with the bath temperature is identified as the temperature perceived by the first Rindler frame. In this analysis they studied both particle number computation by Bogoliubov technique and detector response.…”
Section: Introductionmentioning
confidence: 88%
“…The first example that we consider, is a Rindler observer, who is moving through a thermal bath, with an uniform acceleration. This model has been studied earlier not only in the perspective of Unruh detector [16,22], but also the calculation of particle number, seen from Rindler observer, has been done [14,15]. Consequently it has been argued in [15] that both ways yield the same result.…”
Section: Rindler Observer In Thermal Bathmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work we are going to study the radiative process of two entangled accelerated atoms, coupled to a background scalar field, in a thermal bath. The transition probability corresponding to single accelerated observers in thermal bath are estimated in [45,46], considering two-level Unruh-deWitt detectors (where in [47] the scenario for a rotating detector in thermal bath is considered). In the derivation of [46] the Green's function, which is essential for the calculation, is constructed from the Minkowski modes with a Rindler coordinate transformation.…”
Section: Introductionmentioning
confidence: 99%